2021
DOI: 10.3389/fimmu.2021.611474
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Holo-Beta-Lactoglobulin Cross-Protects Against Pollen Allergies in an Innate Manner in BALB/c Mice: Potential Model for the Farm Effect

Abstract: The lipocalin beta-lactoglobulin (BLG) is a major protein compound in cow’s milk, and we detected it in cattle stable dust. BLG may be a novel player in the farm protective effect against atopic sensitization and hayfever. In previous studies, we demonstrated that only the ligand-filled holo-form of BLG prevented sensitization to itself. Here, we investigated whether holo-BLG could, in an innate manner, also protect against allergic sensitization to unrelated birch pollen allergens using a murine model. BALB/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 67 publications
4
38
0
Order By: Relevance
“…It has been proposed that retinoic acid or iron‐quercetin would bind to T‐cell and B‐cell receptors and suppress immunogenicity and allergenicity of Bos d 5 80,81 . Based on a study in a mouse model, it was also suggested that ligand‐bound Bos d 5 was able to protect against allergic sensitization to unrelated birch pollen allergens 82 …”
Section: Lipocalinsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that retinoic acid or iron‐quercetin would bind to T‐cell and B‐cell receptors and suppress immunogenicity and allergenicity of Bos d 5 80,81 . Based on a study in a mouse model, it was also suggested that ligand‐bound Bos d 5 was able to protect against allergic sensitization to unrelated birch pollen allergens 82 …”
Section: Lipocalinsmentioning
confidence: 99%
“… 80 , 81 Based on a study in a mouse model, it was also suggested that ligand‐bound Bos d 5 was able to protect against allergic sensitization to unrelated birch pollen allergens. 82 …”
Section: Lipocalinsmentioning
confidence: 99%
“…The concept of targeted micronutrition to correct micronutritional deficiencies in immune cells of allergic patients, the main attribute of mode-of-action of loaded beta-lactoglobulin (holoBLG), has been unravelled only recently [3][4][5][6]. There are multiple studies showing that atopy is associated with iron deficiencies [7][8][9][10][11] and/or vitamin deficiencies [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to in vitro experiments and mouse models [11,18], the efficacy of holo-BLG in allergic patients has so far been investigated in two clinical pilot trials. In a first randomised, double-blind, placebo-controlled trial, a total of 20 female patients K Targeted micronutrition for allergic patients-possible applications of a food for special medical purposes 151 mini-review with birch pollen allergy were enrolled and received holo-BLG or placebo daily for 6 months (including the birch pollen season).…”
Section: Holo-blg-targeted Micronutrition Of Immune Cells Leads To Immune Resiliencementioning
confidence: 99%